Optical inspection of smartphone camera modules by near-infrared low-coherence interferometry - Lee, Chang-Yun (2018)
High-resolution cameras used for smartphones are comprised of multiple aspheric lenses, a spectral filter, and a semiconductor image sensor, which are packaged together into a single module with tight geometrical tolerances. We investigated the technical possibility of near-infrared low-coherence interferometry for nondestructive geometrical inspection of the complex camera module to examine the inside packaging state. This tomographic scheme enabled us to measure the relative axial position of each inside component and also the lateral surface profile of the image sensor, allowing for comprehensive three-dimensional quality assurance of the whole camera module during the packaging process.